How Microglia Manages Non-cell Autonomous Vicious Cycling of Aβ Toxicity in the Pathogenesis of AD - Seol, YunHee; Ki, Soomin; Ryu, Hannah L.; Chung, Sooyoung; Lee, Junghee; Ryu, Hoon (Frontiers in Molecular Neuroscience, 2020)
Alzheimer’s Disease (AD) is a progressive neurodegenerative disease and a common form of dementia that affects cognition and memory mostly in aged people. AD pathology is characterized by the accumulation of b-amyloid (Ab) senile plaques and the neurofibrillary tangles of phosphorylated tau, resulting in cell damage and neurodegeneration. The extracellular deposition of Ab is regarded as an important pathological marker and a principal agent of neurodegeneration. However, the exact mechanism of Ab-mediated pathogenesis is not fully understood yet. Recently, a growing body of evidence provides novel insights on the major role of microglia and its non-cell autonomous cycling of Ab toxicity. Hence, this paper provides a comprehensive overview of microglia as a significant player in uncovering the underlying disease mechanisms of AD.